2007
DOI: 10.1021/ol0713234
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Na− and K−C π-Interactions on the Structure and Binding of M3(sol)n(BINOLate)3Ln Catalysts

Abstract: Shibasaki's heterobimetallic complexes M 3 (THF) n (BINOLate) 3 Ln [M = Li, Na, K, Ln = lanthanide (III)] are among the most successful asymmetric Lewis acid catalysts. Why does M 3 (THF) n (BINOLate) 3 Ln readily bind substrates when M = Li but not when M = Na or K? Structural studies herein indicate Na-and K-C cation-π interactions and alkali metal radius may be more important than even lanthanide radius. Also reported is a novel polymeric [K 3 (THF) 2 (BINOLate) 3 Yb] n structure that provides the first evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…Salvadori reported that YbNaB does not bind water, and related observations were made by Shibasaki and Aspinall . We found that the DMF formyl C–H shifted over 4 ppm in the presence of YbLiB in THF, but no LIS was observed in the presence of RENaB (RE = Yb and Eu) or YbKB under identical conditions . Further insight came from the SC-XRD studies of anhydrous RENaB (RE = La III and Eu III ).…”
Section: Understanding and Expansion Of The Catalysis Of Shibasaki’s ...supporting
confidence: 68%
See 1 more Smart Citation
“…Salvadori reported that YbNaB does not bind water, and related observations were made by Shibasaki and Aspinall . We found that the DMF formyl C–H shifted over 4 ppm in the presence of YbLiB in THF, but no LIS was observed in the presence of RENaB (RE = Yb and Eu) or YbKB under identical conditions . Further insight came from the SC-XRD studies of anhydrous RENaB (RE = La III and Eu III ).…”
Section: Understanding and Expansion Of The Catalysis Of Shibasaki’s ...supporting
confidence: 68%
“…(right) Two space-filling models viewed down the C 3 -axes with the 3-H protons in blue. Reproduced with permission from ref . Copyright 2007 American Chemical Society.…”
Section: Understanding and Expansion Of The Catalysis Of Shibasaki’s ...mentioning
confidence: 99%
“…Walsh and co-workers elucidated the X-ray crystal structures of Na 3 (THF) in (BINOLate) 3 La and K 3 (THF) n (BINOLate) 3 Yb in which respective Na + •••naphthyl and K + •••naphthyl interactions were observed (Scheme 147c). 409 The authors speculated that these interactions are responsible for the coordination ability of the catalysts, causing the alkali metal dependence of the product stereochemistry. 433 4.1.2.…”
Section: Alkali Metal Cation-assisted Reactionsmentioning
confidence: 99%
“…Furthermore, use of molecular sieves as coadditive provided 82% enantioselectivity. On the basis of the control experiments and the previous studies, they speculated that after addition of NaI, an alkali metal exchange would occur to afford a La–Li 2 –Na–L 3 complex, which would slightly modify the asymmetric environment, thereby leading to better results.…”
Section: Additive Effects On Metal-catalyzed Asymmetric Reactionsmentioning
confidence: 99%